Legal Protection of Amal Usaha Muhammadiyah Assets at the Regional Leadership of Muhammadiyah Bukittinggi - Dinda Mariska; Mairul Mairul (SEAN Institute, 2026)
Muhammadiyah, as one of the largest Islamic orgnganizations in Indonesia, manages thousands of strategic assets through its charitable endeavors (Amal Usaha Muhammadiyah or AUM) to improve community welfare. However, many of these assets face legal uncertainties and incomplete ownership documentation, creating a high potential for future disputes. This study aims to identify the factual conditions of legal protection for AUM assets under the Regional Leadership of Muhammadiyah (PDM) Bukittinggi and to analyze the main inhibiting factors in its implementation. This research utilizes an empirical legal approach with a descriptive-analytical method, employing field interviews and legal literature reviews for data collection. The results indicate that while the assets are actively utilized for educational, social, and religious purposes, formal legal documentation remains partially incomplete. This vulnerability is primarily constrained by the absence of uniform internal regulations and limited administrative human resources, although the organization has proactively implemented empirical security measures such as appointing nazhir waqf and transferring personal ownership titles to the official organization. In conclusion, achieving optimal legal protection requires the acceleration of asset legalization, the establishment of definitive internal guidelines, and consistent capacity building. These findings provide significant implications for improving the institutional governance of non-governmental organizations, ensuring asset security for sustainable community development.